Digital breast tomosynthesis for early detection of malignant breast microcalcification: A hospital-based cross-sectional study - Showkat, Mst. Syeeda; Bhowmik, Bishwajit; Sultana, Syeda Naheed; Shirin, Mahbuba; Sharmin, Shohaila; Sarkar, Ashis Kumar; Chowdhury, Parisa (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Breast cancer is the leading cause of cancer-related deaths in women. Early detection by screening is crucial for improved survival. Digital breast tomosynthesis (DBT) may offer better visibility than conventional screening. This study aims to assess the diagnostic accuracy of DBT in detecting malignant breast microcalcifications compared to histopathological findings. Methods: This cross-sectional study was done at the Department of Radiology and Imaging, Bangabandhu Sheikh Mujib Medical University, Dhaka, from July 2022 to June 2023 and enrolled 35 women suspected of having breast cancer. Each patient underwent DBT and histopathology tests. The diagnostic accuracy of DBT in detecting malignant breast microcalcifications was assessed compared to the gold standard of histopathology. Results: The average age of the participants was 48.6 years. Palpable breast lumps (91.4%) were the most common clinical presentation. Among them, 80% had malignant microcalcifications diagnosed by DBT, primarily with linear (40.0%) and segmental (28.6%) distribution. Histopathology identified 80% of cases as malignant, with ductal carcinoma in situ (34.3%) being the most prevalent type. DBT demonstrated high sensitivity (100%) and specificity (85.7%) in detecting malignant microcalcifications, resulting in an overall accuracy of 97.1%. Conclusions: DBT has high diagnostic accuracy for detecting malignant breast microcalcifications and can be considered a valid tool for the early detection of breast microcalcifications, particularly in the context of diagnosing breast cancer.